2013
DOI: 10.2190/wr.17.3-4.e
|View full text |Cite
|
Sign up to set email alerts
|

Whistleblower Laws: State or Federal Protection?

Abstract: This article will discuss the unique complexities associated with whistleblower laws and programs in the United States. It will focus on discussion of the myriad of current federal and state laws created because of concern over risks in this area. The goal of this article is to compare state and federal legislation, for the purpose of identifying the states that offer the best protection to whistleblowers as well as identifying any states that offer better protection to whistleblowers than federal law currentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Most of the studies were in the US context as a unit of analysis. Within this, few studies have compared the federal legislation with the state legislature and attempted to identify any states that offer better protection to whistleblowers than federal law currently provides (Goza, Tyner, & Johnson, 2014). Merely one paper under this theme has published in Indian journal where it has been revealed that legislation for whistleblower protection vary widely across nations with the US A delivering the best protection to whistleblowers trailed by Australian whistleblower protection laws and, then, South Africa; India, China and Indonesia lag considerably behind in having a sound whistleblower mechanism (Sharma, Kanojia, & Sachdeva, 2018).…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…Most of the studies were in the US context as a unit of analysis. Within this, few studies have compared the federal legislation with the state legislature and attempted to identify any states that offer better protection to whistleblowers than federal law currently provides (Goza, Tyner, & Johnson, 2014). Merely one paper under this theme has published in Indian journal where it has been revealed that legislation for whistleblower protection vary widely across nations with the US A delivering the best protection to whistleblowers trailed by Australian whistleblower protection laws and, then, South Africa; India, China and Indonesia lag considerably behind in having a sound whistleblower mechanism (Sharma, Kanojia, & Sachdeva, 2018).…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…According to Goza (2014), whistle-blowing is an act with the intention of the disclosure with the organisation's information that related to wrongdoings. However, Agbeja and Sokunle (2016) said that whistle-blowing action is an exposure to wrongful and unauthorised act that is then placed under control by authorised people in charge.…”
Section: Intention Towards the Whistle-blowingmentioning
confidence: 99%